(3GdSfO GdUMjM GdMSf aj eBKQ ehdGfG CHj GdMSfs - (3eMeO Hf CMeO Hf eMeO Hf eQRhb GdYLjSj CHh YHO Gddg , GHf eQRhb , TeS GdOjf,J (B781 (3g` s
(3ChdgG (B:s
(3hef gPg GdChUGa hGdZjH dcfi QCjJ JNdjOgG ai GdOaGJQ hSejJg GdeSfO GdUMjM GdMSf ai eBKQ ehdGfG CHj GdMSf s
(3BNQgG (B:s
(3hebGege GdCYdi ef GdLejY eNUhU HCJe GdSdGe hQMeI Gddg JYGdi hHQcGJg , hYPQ ef ESJYLd JbjjOg ai JSY BNQgG ChGFd TgQ QeVGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJUha hGdBOGH GdTQYjIs